In vitro inhibition of human nucleoside transporters and uptake of azacitidine by an isocitrate dehydrogenase-2 inhibitor enasidenib and its metabolite AGI-16903. (3rd October 2019) - Tong, Zeen; Yerramilli, Usha; Yao, Sylvia; Young, James D.; Hoffmann, Matthew; Surapaneni, Sekhar
Abstract: 1. The present study investigated inhibitory effects of enasidenib and its metabolite AGI-16903 on (a) recombinant human nucleoside transporters (hNTs) in hNT-producing Xenopus laevis oocytes, and (b) azacitidine uptake in a normal B-lymphoblast peripheral blood cell line (PBC) and acute myeloid leukemia (AML) cell lines. 2. Enasidenib inhibited hENT1, hENT2, hENT3, and hENT4 in oocytes with IC50 values of 7, 63, 27, and 76 μM, respectively, but exhibited little inhibition of hCNT1-3. AGI-16903 exhibited little inhibition of any hNT produced in oocytes. 3. Azacitidine uptake was more than 2-fold higher in AML cells than in PBC. Enasidenib inhibited azacitidine uptake into OCI-AML2, TF-1 and PBC cells in a concentration-dependent manner with IC50 values of 0.27, 1.7, and 1.0 µM in sodium-containing transport medium, respectively. 4. IC50 values shifted approximately 100-fold higher when human plasma was used as the incubation medium (27 µM in OCI-AML2, 162 µM in TF-1, and 129 µM in PBC), likely due to high human plasma protein binding of enasidenib (98.5% bound). 5. Although enasidenib inhibits hENTs and azacitidine uptake in vitro, plasma proteins attenuate this inhibitory effect, likely resulting in no meaningful in vivo effects in humans.